Kinerja Sekretariat Jenderal Dalam Menindaklanjuti Pengaduan Pada Komisi X Dewan Perwakilan Rakyat Republik Indonesia - Salwa Khoirunnisa; Qiqi Asmara (Jurnal Relasi Publik, 2024)
The government essentially provides services to the community and is required to serve the community and create conditions so that it has an impact on the community to develop, one of which is education. Through the Secretariat General, public complaints about education issues are submitted to Commission X of the DPR RI. The background for choosing this title was due to the increase in complaints submitted by the public regarding education, as well as a decrease in the performance of the Secretariat General of the DPR RI. The research objective is to identify and analyze the performance of the Secretariat General in following up on complaints to Commission X DPR RI. This study uses the theory of Agus Dharma (2004) with three measurement indicators that determine success, namely, (1) quantity, (2) quality, and (3) timeliness. This study used a qualitative research method with a descriptive approach. This study uses a way to collect data by making observations to collect data at the Secretariat General and Commission X DPR RI. The results on indicator (1) Quantity, the number of reports that have been completed by Commission X DPR RI are not submitted back to the Secretariat General of the DPR RI. (2) Quality, there is no clear information regarding the follow-up of letters submitted through the websitewebsite, human resources need to conduct training on the applied information technology system, Commission X DPR RI is one that receives the most complaints in 2020-2021, (3) Timeliness, the time needed is very long because of the difficulty level of the complaint letter, correction of the results of the analysis until the letter can be submitted to Commission X DPR RI. The conclusion of this study is that in following up on complaints to Commission X DPR RI, reports that have been completed by Commission X DPR RI are not submitted back to the Secretariat General.